Contribution of Rhizobium–Mycorrhiza–Merapi-indigenous Rhizobacteria Association on Growth and Yield of Three Cultivars Soybean Cultivated on Coastal Sandy Soil - Linda Kusumastuti; Agung Astuti; Sarjiyah Sarjiyah (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
A study was conducted to examine the effect of inoculum association between Rhizobium sp., mycorrhizae and Merapi-indigenous Rhizobacteria on the growth and yield of 3 soybean cultivars, and to determine the best inoculum and cultivars for soybean cultivation on coastal sandy soil. The study was conducted in the Agro-biotechnology and Research Laboratory and experimental station of Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta during the period of September 2015 to June 2016. Experiments were conducted by using coastal sandy soil as planting medium in polybags by employing 4 x 3 factorial experiments, arranged in completely randomised design, and placed under the field condition. The first factor used was inoculation treatment consisted of 4 combination of inoculums: (1) Rhizobium sp. – mycorrhizae, (2) Rhizobium sp. – Merapi-indigenous Rhizobacteria, (3) Rhizobium sp. – mycorrhizae – Merapi-indigenous Rhizobacteria, and (4) without inoculation. The second factor was soybean cultivars consisted of 3 varieties: (1) Grobogan, (2) Detam-1, and (3) Petek. Observation was carried out on nodulation, mycorrhizal effect, Rhizobacterial population dynamics, plant growth and yield. The results showed that Rhizobium sp.–mycorrhizae inoculated on Petek increased root growth, leaf area and yield (5,97 tonnes/ha). Rhizobium sp.–mycorrhizae inoculation only increased diameter of nodules. It was also observed that the best soybean cultivar for coastal sandy soil was Petek.